Socioeconomic Inequalities in Nonuse of Seatbelts in Cars and Helmets on Motorcycles among People Living in Kurdistan Province, Iran. - Ghobad Moradi; Hossein Malekafzali Ardakani; Reza Majdzadeh; Farzam Bidarpour; Kazem Mohammad; Kourosh Holakouie-Naieni (Tehran University of Medical Sciences, 2014)
The aim of this study was to determine the socioeconomic inequalities in nonuse of seatbelts in cars and helmets on motorcycles in Kurdistan Province, west of Iran, 2009.The data used in this study was collected from the data gathered in non-communicable disease surveillance system (NCDSS) in 2009 in Kurdistan. A total of 1000 people were included in this study. The outcome variable of this study was the nonuse of seatbelts and helmets. The socio-economic status (SES) was calculated based on participants' residential area and assets using Principal Component Analysis (PCA) method. The concentration index, concentration curve, and comparison of Odds Ratio (OR) in different SES groups were used to measure the socioeconomic inequalities using logistic regression. In order to determine the contribution of determinants of inequality, decomposition analysis was used.The prevalence of nonuse of seatbelts in cars and helmets on motorcycles were 47.5%, 95%CI [44%, 55%], respectively. The Concentration index was -0.097, CI [-0.148, -0.046]. The OR of nonuse of seatbelts in cars and helmets on motorcycles in the richest group compared with the poorest group was 0.39, 95%CI [0.23, 0.68]. The results of the decomposition analysis showed that 34% of inequalities were due to SES, 47% were due to residential area, and 12% were due to unknown factors.There is a reverse association between SES and nonuse of seatbelts in cars and helmets on motorcycles. This issue must be considered while planning to reduce traffic accidents injuries.